Technology acceptance application model on internet banking service in BRI Bank Denpasar Indonesia - Melaning, Ari; Giantari, I.G.A.K. (International research journal of management, IT and social sciences, 2019)
This study aims to explain the effect of perceived usefulness, and perceived ease of use, on attitude toward using, and behavioral intention of use at BRI banks Denpasar. The technique used to test the research hypothesis uses Structural Equation Modeling (SEM) analysis techniques using SMARTPLS assistance, using IBM SPSS Statistics 22. The population in this study were all BRI Bank customers in Denpasar who used Internet Banking, the number of samples in this study was 150 respondents, who were taken using Purposive Sampling techniques. The results showed that (1) the attitude toward using had a positive and significant effect on the behavioral intention of use (2) perceived ease of use had a positive and significant effect on attitude toward using (3) perceived usefulness had a positive and significant effect on the behavioral intention of use. (4) perceived ease of use has a positive and significant effect on the behavioral intention of use (5) perceived usefulness has a positive and significant effect on attitude toward using. (6) attitude toward using can mediate the relationship between perceived usefulness to the behavioral intention of use. (7) the attitude toward using can mediate the relationship between perceived ease of use on the behavioral intention of use.